Literature Review: The Application of Think Talk Write (TTW) Model to the Writing Skills of Learners in Elementary School - Binta Risqia Estafasari; Sarwi Sarwi; Syaiful Amin; Sri Sumartiningsih; Agus Yuwono (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2025)
Writing is one of the four main components of language skills, namely speaking, listening, reading and writing. Writing has a very important role in conveying concepts and ideas in depth and structure, both in the form of fiction and non-fiction. This confirms that the ability to write is not only a basic skill in communication, but also an important means of expressing human thoughts and emotions. This research is a literature review that involves analysis of various articles that examine the Think Talk Write (TTW) model and writing skills. The articles used are sourced from Google Scholar and Scopus.  The articles used were articles published between 2019 and 2024 and 25 relevant articles were found. This research aims to analyze the application of the Think Talk Write (TTW) learning model to the writing skills of elementary school students in several types of text writing material in Indonesian language subjects. Apart from that, this research also discusses the application of the Think Talk Write (TTW) model with the help of several types of learning media. Based on data analysis, it is proven that the Think Talk Write (TTW) model improves students' writing skills in elementary schools.